Evaluasi Penataan Terminal Kota Teluk Kuantan Kabupaten Kunatan Singingi - Tria Anggraini; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The structur of the bus station cannot be separated from the management of bus station conducted by relevant institute. Bus station, if explained in the section no. 22 year 2009 about traffic and land transportation is a transport infrastructure for the purpose of bring the passenger, movement intra or inter modal transportation and to arrange the arrival and departure of the public and distribution of goods.The purpose of this research was to determine arrangement of bus station in the town of Teluk Kuantan, Kuantan Singingi Regency. And the other hand , to identity the factors that influenced the evaluation of arrangement of Bus Station in Teluk Kuantan, Kuantan Singingi Regency. The concept of the theory the writer used is the concept of evaluation theory by William Dunn. This research is a qualitative in showed by using descriptive data. In this research, the writer used interview techniques, observation, and documentation, By used of Key informants as a source of information.The result showed that the evaluation of arrangement of Bus Station in Teluk Kuantan of Kuantan Singingi Regency was ineffective, inefficient , insufficient, and inresponsive. In addition, there are so many factors that influenced Bus Station Arrangement, like human resoources and operasional values that are too insignificant.Keyword : Evaluation of Arrangement of Bus Station in Teluk Kuantan ,Kuantan Singingi Regency